2019
DOI: 10.1002/jmr.2825
|View full text |Cite
|
Sign up to set email alerts
|

A novel electroconductive interface based on Fe3O4 magnetic nanoparticle and cysteamine functionalized AuNPs: Preparation and application as signal amplification element to minoring of antigen‐antibody immunocomplex and biosensing of prostate cancer

Abstract: In this study, a novel electroconductive interface was prepared based on Fe3O4 magnetic nanoparticle and cysteamine functionalized gold nanoparticle. The engineered interface was used as signal amplification substrate in the electrochemical analysis of antibody‐antigen binding. For this purpose, biotinilated‐anti‐prostate‐specific antigen (PSA) antibody was bioconjugated with iron oxide magnetic nanoparticles (Fe3O4) and drop‐casted on the surface of glassy carbon electrode (GCE). Also, secondary antibody (HRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Prostate cancer is the most significant reason for deaths in men, outside of lung cancer. The clinical examination of cancer proteins or biomarkers is extremely significant in early examination and monitoring of recurrence of disease after treatment [ 3 ]. In addition to during prognosis, biomarkers usually increased a lot of clinical importance because of their extensive spectra in the identification, elimination, early diagnosis and cure of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is the most significant reason for deaths in men, outside of lung cancer. The clinical examination of cancer proteins or biomarkers is extremely significant in early examination and monitoring of recurrence of disease after treatment [ 3 ]. In addition to during prognosis, biomarkers usually increased a lot of clinical importance because of their extensive spectra in the identification, elimination, early diagnosis and cure of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary antibody (HRP-Ab2) encapsulated on AuNPs covered by cysteamine was fixed on the GCE modified electrode. Under ideal experimental circumstances, a detection limit of 0.001 µg.L −1 of PSA was achieved ( Farshchi et al, 2020 ). In another study, Mahani et al, reported.…”
Section: Functionalization With Recognition Elements On Aunps (Transd...mentioning
confidence: 99%
“…MNPs were prepared by the conventional co-precipitation process. 41 on the CV technique. 43,44 According to Figures S7 and S8 (see supporting information), anodic and cathodic peak currents of P(L-Arg/Tb) and PDA-MNPs/L-Arg/Tb vary with scan rate, and by progress of scan rate, the peak separation (ΔE) increases, (ΔE p , is calculated by E pc À E pa ).…”
Section: Preparation Of the Modified Electrodesmentioning
confidence: 99%